Estimating setback distances for a threatened, cryptic, data-sparse migratory shorebird - Birgita D. Hansen; Jodie Honan; Don Stewart; Judi R. Walters; Michael A. Weston (PLoS ONE, 2025)
Cryptic fauna species using highly modified habitats face many conservation challenges, with disturbance from human use being an ongoing issue across many global settings. Setbacks or buffers are a key planning tool for protecting habitat, and are often specified under law. However, for many species using modified and urban habitats there are no published data on how wide setbacks should be. Latham’s Snipe (Gallinago hardwickii) is a case in point. It is a threatened, cryptic, migratory shorebird that breeds in Japan and spends its non-breeding season almost entirely in Australian wetlands and grasslands. Many sites used by snipe are within urban areas, potentially triggering protections under national law and there is an urgent need for information on setbacks to inform planning and conservation management. The aim of this project was to derive transparent, scientifically-derived buffer recommendations for mitigating disturbance to Latham’s Snipe, by estimating Alert Distances (AD; the first sign of behavioural disruption associated with human proximity) from measures of flush distances (FIDs; the distance at which flight occurs). ADs are almost impossible to observe in this cryptic species which uses dense habitat. We used 1529 FIDs to estimate AD from: (1) a within-species regression of FID against the few available ADs for this species (n =  8), and (2) cross-species associations between AD and FID of Scolopacidae from analysis of an unpublished dataset. FIDs varied between site and observers, so we resampled using bootstrapping to account for this variation and produce estimates of AD. Based on these estimates, we recommend minimum buffer widths between 75 - 110 m, which would prevent 80 - 95% of vigilance responses by Latham’s Snipe, respectively. The methods we employ may be useful in determining appropriate buffer widths for other cryptic fauna species. These buffers should be monitored for effectiveness and adapted as required.